A Molecular Chameleon for Mapping Subcellular Polarity in an Unfolded Proteome Environment. Issue 25 (8th January 2020) - Owyong, Tze Cin; Subedi, Pramod; Deng, Jieru; Hinde, Elizabeth; Paxman, Jason J.; White, Jonathan M.; Chen, Weisan; Heras, Begoña; Wong, Wallace W. H.; Hong, Yuning
Abstract: Environmental polarity is an important factor that drives biomolecular interactions to regulate cell function. Herein, a general method of using the fluorogenic probe NTPAN‐MI is reported to quantify the subcellular polarity change in response to protein unfolding. NTPAN‐MI fluorescence is selectively activated upon labeling unfolded proteins with exposed thiols, thereby reporting on the extent of proteostasis. NTPAN‐MI also reveals the collapse of the host proteome caused by influenza A virus infection. The emission profile of NTPAN‐MI contains information of the local polarity of the unfolded proteome, which can be resolved through spectral phasor analysis. Under stress conditions that disrupt different checkpoints of protein quality control, distinct patterns of dielectric constant distribution in the cytoplasm can be observed. However, in the nucleus, the unfolded proteome was found to experience a more hydrophilic environment across all the stress conditions, indicating the central role of nucleus in the stress response process. Abstract : Under stress : Reported is a strategy based on a multi‐responsive probe, in combination with spectral phasor analysis, to monitor the change of subcellular polarity in response to protein unfolding. Under stress conditions that disrupt different checkpoints of protein quality control, distinct patterns of dielectric constant distribution across the cell can be observed.